Determinação e refinamento de estruturas tridimensionais da proteína SurE de Xylella fastidiosa - Machado, Agnes Thiane Pereira (2013)
This dissertation presents the processing of seven image datasets and the determination and refinement of two protein structures of Sure (stationary phase survival protein E)from Xylella fastidiosa(XfSurE). The crystals were obtained by the research groupof Prof.Dr.RicardoApariciowith theprotein produced by the group of Profa. Dra.Anete Pereira de Souza, both from the State University of Campinas.Xylella fastidiosa strain 9a5c is aplague bacterium that causes a disease called Citrus Variegated Chlorosis (CVC) in orange grove; itwas the first bacterium to have its genome completely sequenced in Brazil. Studies show that this protein has several functions, amongst them, of a nucleotidase able to dephosphorylate various ribo anddeoxyribonucleic 5-monophosphates and ribonucleoside 3-monophosphatesto inorganic phosphate and nucleosides. Seven different sets of diffraction images were processed,four of them presented rings from ice diffraction. All structures have space group C2, but there are four different unit cells.Molecular replacement was performed with Phaser program and only two sets of images had their three-dimensional structures refined in an iterative process with the programs Coot and Phenix, which were subsequently largely validated. One of them shows a tetramer and the other a dimer in the asymmetric unit. During refinement, Mn+2, I- and PO43-ions were modeled. Comparisons between XfSurE and CbSurE (the correspondent protein fromCoxiella burnetti) indicate that XfSurE isin open conformation, unlike CbSurE. The protein shows the characteristic Rossmann fold-like, with the tetramerizationloop and C-terminal projection into the counter-monomer.